Shia: Its History and Development in Indonesia - Moh Hasyim (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
Shiah becomes a new problem in Indonesia after hundreds years of living together. Currently, treatment to Shiah tends to violate the principles of religious freedom. Therefore, it is necessary to know, how the history of the emergence of Shiah and its development in Indonesia? This is a library research using a critical analysis approach. This study found that the Syiah is a religious ideology which refers to the views of Saidina Ali (the fourth khalifat) and his descendants. This teaching emerged since the beginning of the khulafaurasidin. Shiah has developed dozens of religiousstreams due to disagreement and differences on the idea of Imamah. There are four stages of Shiah development in Indonesia, namely: Firstly, along with the arrival of Islam in Indonesia; Secondly, after the Islamic revolution in Iran; Thirdly, through Indonesian Muslim Intellectuals who studied in Iran, and Finally, during the open era there was an establishment of as association Jamaah Ahlul Bai’t Indonesia.